A Pediatric Emergency Department Intervention to Increase Contraception Initiation Among Adolescents. (25th October 2018) - Hoehn, Erin F.; Hoefgen, Holly; Chernick, Lauren S.; Dyas, Jenna; Krantz, Landon; Zhang, Nanhua; Reed, Jennifer L.
Abstract: Background: The pediatric emergency department (PED) provides care for adolescents at high risk of unintended pregnancy, but little is known regarding the efficacy of PED‐based pregnancy prevention interventions. The objectives of this PED‐based pilot intervention study were to 1) assess the rate of contraception initiation after contraceptive counseling and appointment facilitation in the PED during the study period, 2) identify barriers to successful contraception initiation, and 3) determine adolescent acceptability of the intervention. Methods: This pilot intervention study included females 14 to 19 years of age at risk for unintended pregnancy. Participants received standardized contraceptive counseling and were offered an appointment with gynecology. Participants were followed via electronic medical record and phone to assess contraception initiation and barriers. Chi‐square tests were used to examine the association between contraception initiation and participant characteristics. Results: A total of 144 patients were eligible, and 100 were enrolled. In the PED, 68% (68/100) expressed interest in initiating hormonal contraception, with 70% (48/68) of interested participants indicating that long‐acting reversible contraception (LARC) was their preferred method. Twenty‐five percent (25/100) of participants initiated contraception during the study period, with 19 participants starting LARC. Thirty‐nine percent (22/57) of participants who accepted a gynecology appointment attended that appointment. Barriers to follow‐up include transportation and inconvenient follow‐up times. Participants were accepting of the intervention with 93% agreeing that the PED is an appropriate place for contraceptive counseling. Conclusions: PED contraceptive counseling is acceptable among adolescents and led to successful contraception initiation in 25% of participants. The main barrier to contraception initiation was participant follow‐up with the gynecology appointment.